2018
DOI: 10.3390/met8020088
|View full text |Cite
|
Sign up to set email alerts
|

On the PLC Effect in a Particle Reinforced AA2017 Alloy

Abstract: Abstract:The Portevin-Le Châtelier (PLC) effect often results in serrated plastic flow during tensile testing of aluminum alloys. Its magnitude and characteristics are often sensitive to a material's heat treatment condition and to the applied strain rate and deformation temperature. In this study, we analyze the plastic deformation behavior of an age-hardenable Al-Cu alloy (AA2017) and of a particle reinforced AA2017 alloy (10 vol. % SiC) in two different conditions: solid solution annealed (W) and naturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 56 publications
(83 reference statements)
0
18
0
Order By: Relevance
“…This serration-flow behaviour is called the Portevin-Le Chatelier (PLC) effect during the plastic deformation of the material [28]. The substitute and interstitial alloys, such as Al alloys [42], carbon steel [43], and copper alloys [44], tend to demonstrate PLC behaviour during tensile loading [45]. The PLC effect is related to pinning and unpinning processes, where the pinned process has occurred when the dislocation is stuck by obstacles formed from the forest dislocations and grain boundaries.…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This serration-flow behaviour is called the Portevin-Le Chatelier (PLC) effect during the plastic deformation of the material [28]. The substitute and interstitial alloys, such as Al alloys [42], carbon steel [43], and copper alloys [44], tend to demonstrate PLC behaviour during tensile loading [45]. The PLC effect is related to pinning and unpinning processes, where the pinned process has occurred when the dislocation is stuck by obstacles formed from the forest dislocations and grain boundaries.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…The frequencies of serration are different because of the stress fields of the grain size, in which the serration frequency is high for the as-welded sample. After rolling, the serration causes the stress to increase with increased rolling percentage because of the pinning effect [42]. Thus, the strain hardening increasing during rolling results in decreasing crystallite size and lattice strain for the sample.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…They observed characteristic oscillations on strain-stress curves in aluminum-based alloys and low-carbon steels [1]. Since then, the Portevin-Le Chatelier effect (PLC) has been extensively studied in copper and aluminum-based alloys during tensile or compression tests [2][3][4][5]. However, in the case of steels the PLC effect was studied rarely [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Clarke and Hinton [2] pointed out that these oscillations may be misinterpreted as special material characteristics. However, several researchers have observed and concluded that the serration phenomenon is actually a material property and it depends on the material type, strain rate and temperature [7,[10][11][12]15,21,26,27]. Nevertheless, the effect of auto-tuning on the serration behavior has not been reported so far.…”
Section: The Effect Of Auto-tuningmentioning
confidence: 99%
“…The plastic deformation in metals and alloys is mainly attributed to the nucleation and motion of dislocations [20]. The PLC effect has been investigated by stress and strain-controlled tensile tests as well as digital image correlation and acoustic emission [21]. Recently some researchers have reported the PLC effect under compressive loading as well [9].…”
Section: Introductionmentioning
confidence: 99%